Case report: Identification of Hepatitis B Virus in the cerebrospinal fluid of neuromyelitis optica spectrum disorders and successful treatment with ofatumumab and inebilizumab - Cai, Linjun; Liu, Xu; Zhou, Hongyu; Li, Jinmei; Zhou, Dong; Hong, Zhen (Frontiers in Immunology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare demyelinating disease of the central nervous system primarily affecting the optic nerves, spinal cord, and brainstem. Viral infection may trigger NMOSD. Here, we report the case of a 34-year-old female presenting with a range of symptoms including nausea, vomiting, dysphagia, choking, and fatigue with unsteady gait, diplopia, hearing loss, left-sided facial paralysis, breathing difficulties, and hoarseness of voice. Her HBV DNA concentration, as determined by quantitative PCR analysis, exceeded 5×107 IU/ml in serum and 4.48×102 IU/ml in CSF. Next-generation sequencing of CSF revealed 1,528 HBV sequences in DNA analysis and 6 sequences in RNA analysis. Serum aquaporin-4 antibody (AQP4-Ab) titer was 1:10, and the CSF titer was 1:3.2. Brain magnetic resonance imaging showed high signal intensities in the brain stem, medulla oblongata, and left middle cerebellar peduncle with mild restricted-diffusion. The patient received antiviral and hepatoprotective medications before the high-dose methylprednisolone pulse therapy. However, the patient did not respond well to the first-line treatment. Subsequently, the patient received ofatumumab and inebilizumab. Throughout the follow-up period, there was a gradual improvement in her neurological symptoms, with no reactivation of hepatitis B or deterioration of liver function observed. Thereby, to the best of our knowledge, we report the first case of successful treatment with ofatumumab and inebilizumab in a patient with NMOSD concurrent with HBV infection.